New directions in natural theology - Pickering, David (Theology, 2021)
This article contrasts natural theology’s vicissitudes in recent centuries with its more promising prospects in contemporary philosophy and theology. It interrogates certain genres of theology regarding their relation to natural theology, focusing on feminist theology, eco-theology, apologetics and the theology of natural law. It concludes with a reflection on the aspects of natural theology that are particularly prominent at present, and asks if the degree of revival currently enjoyed by natural theology may even be the precursor of a greater role in the academy.